Risk factors and characteristics of preoperative heart failure in elderly patients with hip fracture and the influence of anemia on prognosis - Aoying Min; Wei Zhao; Wei Li; Weining Li; Zhiyong Hou; Zhiqian Wang (BMC Musculoskeletal Disorders)
Abstract Background Patients with preoperative acute heart failure (AHF) after hip fracture in the elderly have a worse prognosis. We aim to investigate the characteristics, risk factors and postoperative complications of elderly patients with hip fracture complicated with preoperative AHF. We also looked at the effect of the severity of anemia at admission on the prognosis of the above people. Methods A retrospective study of hip fracture patients (aged ≥ 65) admitted to the Department of Geriatric Orthopaedics, Third Hospital, Hebei Medical University, was conducted from January 2018 to October 2020. We used univariate and multivariate logistic regression to assess risk factors for preoperative AHF. The Kaplan–Meier survival curve shows the relationship between the severity of anemia on admission and all-cause mortality in elderly hip fracture patients with preoperative AHF. Results Out of the 1092 patients, 503 had preoperative AHF and the incidence of it in hip fracture patients was 46.1%. Age, coronary artery disease, chronic atrial fibrillation, Age-Adjusted Charlson Comorbidity Index (ACCI), admission anemia, admission albumin < 40 g/dl, and admission C-reactive protein (CRP) were all significantly different between those with AHF and those without. Multivariate logistic regression analysis revealed that age ≥ 80 years (OR 1.740, 95% CI 1.309–2.313), coronary artery disease (OR 1.417, 95% CI 1.017–1.975), chronic atrial fibrillation (OR 4.010, 95% CI 1.757–9.152), admission anemia (OR 1.433, 95% CI 1.051–1.953) are the independent risk factors for preoperative AHF in elderly patients with hip fracture (p < 0.05). The HF group exhibited a higher incidence of postoperative complications, such as anemia, arrhythmia, NOAF (new‐onset atrial fibrillation), AIS (acute ischemic stroke), electrolyte disturbance and hypoproteinemia. The moderate-to-severe anemia group had a higher incidence of postoperative complications, including deep vein thrombosis of the lower limbs, NOAF, and hypoproteinemia, as well as all-cause mortality. Conclusion Older patients combined with admission anemia, coronary artery disease, chronic atrial fibrillation are more likely to have preoperative AHF after hip fracture. For such patients, early and effective identification and strengthening perioperative management can avoid the occurrence of adverse events. For patients with moderate and severe anemia at admission, timely intervention is recommended to reduce postoperative complications and mortality.